Sex-dependent regulation of mucin gene transcription and airway secretion and mechanics following intra-airway IL-13 in mice with conditional loss of club cell Creb1 - Sponchiado, Mariana; Fagan, Amy; Mata, Luz; Bonilla, Angelina L.; Trevizan-Baú, Pedro; Prabhakaran, Sreekala; Reznikov, Leah R. (Frontiers in Physiology, 2024)
Interleukin 13 (IL-13) is an important effector molecule in allergic asthma. IL-13-mediated mucin hypersecretion requires conversion of secretoglobin-positive club cells into goblet cells through suppression of forkhead box A2 (FOXA2) and induction of SAM pointed domain containing ETS transcription factor (SPDEF). IL-13-mediated mucin hypersecretion may also include modulation of purinergic and muscarinic receptors that control basal and stimulated mucin secretion. We recently found that the transcription factor cAMP response element-binding protein (Creb1) inhibits FOXA2 and modulates mucus secretion in mice. Here we tested the hypothesis that loss of club cell Creb1 in murine airways mitigates the pro-mucin effects of IL-13. Loss of club cell Creb1 augmented IL-13-mediated increases in mRNA for the gel-forming mucins Muc5ac and Muc5b and prevented IL-13-mediated decreases in muscarinic 3 receptor (M3R) mRNA in male airways. In female airways, loss of club cell Creb1 reduced M3R mRNA and significantly blunted IL-13-mediated increases in purinergic receptor P2Y2 (P2ry2) mRNA but did not impact Muc5ac and Muc5b mRNA. Despite changes in mucins and secretion machinery, goblet cell density following cholinergic stimulation was not impacted by loss of club cell Creb1 in either sex. IL-13 treatment decreased basal airway resistance across sexes in mice with loss of club cell Creb1, whereas loss of club cell Creb1 augmented IL-13-mediated increases in airway elastance in response to methacholine. Human "club cell-like" NCI-H322 cells displayed IL-13 signaling components, including IL-13Rα1 and IL-4Rα. Pharmacologic inhibition of CREB reduced IL-13Rα1 mRNA, whereas recombinant CREB decreased IL-4Rα mRNA. Application of IL-13 to NCI-H322 cells increased concentrations of cAMP in a delayed manner, thus linking IL-13 signaling to CREB signaling. These data highlight sex-specific regulation of club cell Creb1 on IL-13-mediated mucin hypersecretion and airway mechanics.